Characterization and management of the thyroid nodule in children, in the Head, Neck and Maxillofacial Surgery Service of the Instituto Nacional de Salud del Niño - Breña, 2000 - 2020 - Broggi Ruiz, Alfredo Giovanni (2022)
Introduction. The thyroid nodule in children is usually asymptomatic, multiple and isolated presentation, with difficulty in establishing the risk of malignancy, especially if it is not palpable. Objective. To determine the epidemiological, clinical and ultrasound characteristics and surgical management of thyroid nodules in patients of the Head, Neck and Maxillofacial Surgery Service of the Instituto Nacional de Salud del Niño (INSN) – Breña, 2000-2020. Methods. Observational, descriptive and retrospective study. The Bethesda classification was used for cytological studies. Qualitative variables were expressed in absolute and relative frequencies; and quantitative variables in measures of central tendency and dispersion. Results. There were 66 cases, the average age was 10.94 ± 0.88 years, 48.5% between 11 and 15 years, 78.8% were female, 89.4% had no family history of cancer. The asymptomatic form predominated (74.2%). Ultrasonographically, 43.9% of nodules were located in the right lobe, single presentation (68.2%) and smaller than two centimeters (43.9%). 82.6% of the 23 Bethesda II cases were hemithyroidectomized and 86.4% of 22 Bethesda VI cases were thyroidectomized. Conclusions. In pediatric patients, thyroid nodules occurred mostly in women aged 11 to 15 years, with no family history of cancer, asymptomatic, located in the right lobe, single and less than two centimeters. Grade II of the Bethesda classification was the most frequent. Hemithyroidectomy was the most used surgical intervention.